Additive Production of a Material Based on an Acrylic Polymer with a Nanoscale Layer of Zno Nanorods Deposited Using a Direct Current Magnetron Discharge: Morphology, Photoconversion Properties, and Biosafety - Dmitry E. Burmistrov (MDPI AG, 2021)
On the basis of a direct current magnetron, a technology has been developed for producing nanoscale-oriented nanorods from zinc oxide on an acrylic polymer. The technology makes it possible to achieve different filling of the surface with zinc oxide nanorods. The nanorods is partially fused into the polymer; the cross section of the nanorods is rather close to an elongated ellipse. It is shown that, with intense abrasion, no delamination of the nanorods from the acrylic polymer is observed. The zinc oxide nanorods abrades together with the acrylic polymer. Zinc oxide nanorods luminesces with the wavelength most preferable for the process of photosynthesis in higher plants. It was shown that plants grown under the obtained material grow faster and gain biomass faster than the control group. In addition, it was found that on surfaces containing zinc oxide nanorods, a more intense formation of such reactive oxygen species as hydrogen peroxide and hydroxyl radical is observed. Intensive formation of long-lived, active forms of the protein is observed on the zinc oxide coating. The formation of 8-oxoguanine in DNA in vitro on a zinc oxide coating was shown using ELISA method. It was found that the multiplication of microorganisms on the developed material is significantly hampered. At the same time, eukaryotic cells of animals grow and develop without hindrance. Thus, the material we have obtained can be used in photonics (photoconversion material for greenhouses, housings for LEDs), and it is also an affordable and non-toxic nanomaterial for creating antibacterial coatings.